2019
DOI: 10.9734/sajrm/2019/v5i230126
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiogram of Pseudomonas aeruginosa Isolated from West African Mud Creeper (Tympanotonus fuscatus)

Abstract: The menace of opportunistic infections arising from food contamination can be tackled with knowledge of agents effective against the etiologic agents. A bacteriological examination was carried out on Tympanotonos fuscatus (West African Mud Creeper) sold at different markets in Port Harcourt, Nigeria with interest on Pseudomonas aeruginosa and their antibiogram using standard microbiological methods. Results showed that parboiled samples had the mean total heterotrophic bacterial counts between 26.33±11.02x106 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…73 P. aeruginosa has been isolated from foods such as the West African Mud Creeper sold in local markets. 74 The one prior study of airborne microbes in Mali found that up to 25% of the bacterial isolates detected were opportunistic human pathogens. 13 Many of the genera phylogenetically related to human pathogens, as well as two of the potential pathogens confirmed at the species level using PCR, exhibited abundance in the smallest particle size fractions (<2.5 μm), highlighting the potential for long-distance transport.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…73 P. aeruginosa has been isolated from foods such as the West African Mud Creeper sold in local markets. 74 The one prior study of airborne microbes in Mali found that up to 25% of the bacterial isolates detected were opportunistic human pathogens. 13 Many of the genera phylogenetically related to human pathogens, as well as two of the potential pathogens confirmed at the species level using PCR, exhibited abundance in the smallest particle size fractions (<2.5 μm), highlighting the potential for long-distance transport.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…The isolates were identified based on microscopy and their cultural as well as biochemical attributes. The bacterial species were identified phenotypically by examining their cultural identities based standard microbiological procedures, as reported by Sampson et al [14] and Akani et al [15]. This involved spreading aliquots of the serially diluted samples over the surface of solid agar plates and incubated at 37ºC for 24-48 hours.…”
Section: Characterization and Identification Of Isolatesmentioning
confidence: 99%
“…Garba et al (2012) found that Pseudomonas had a high sensitivity to Ofloxacin and Gentamicin while simultaneously having a high resistance to Amoxicilin/Clavulanic acid (Augmentin) in their investigation. P. aeruginosa resistance is a serious public health problem, especially because it is a leading source of nosocomial infections in hospitals [16]. The sensitivity pattern of E. coli and Salmonella spp to antibiotics in this study showed that isolates were mostly resistant to Cefixime, Ceftazidime and Cefuroxime with all isolates (100%) resistant to these antibiotics.…”
Section: Resultsmentioning
confidence: 59%
“…The sensitivity of Pseudomonas spp to gentamicin and Ofloxacin in the present study is in agreement with the results of antibiogram of Pseudomonas spp. from the study by Akani et al [16]. The resistance of Pseudomonas spp.…”
Section: Resultsmentioning
confidence: 97%